Relation between plasma ceramides and cardiovascular death in chronic heart failure: A subset analysis of the GISSI‐HF trial. (6th July 2020) - Targher, Giovanni; Lunardi, Gianluigi; Mantovani, Alessandro; Meessen, Jennifer; Bonapace, Stefano; Temporelli, Pier Luigi; Nicolis, Enrico; Novelli, Deborah; Conti, Antonio; Tavazzi, Luigi; Maggioni, Aldo Pietro; Latini, Roberto
Abstract: Aims: Ceramides exert several biological activities that may contribute to the pathophysiology of cardiovascular disease and heart failure (HF). The association between plasma levels of distinct ceramides (that have been previously associated with increased cardiovascular risk) and cardiovascular mortality in patients with chronic HF has received little attention. Methods and results: In a post hoc ancillary analysis of the Gruppo Italiano per lo Studio della Sopravvivenza nella Insufficienza Cardiaca‐Heart Failure (GISSI‐HF; NCT00336336) trial, we randomly selected a sample of 200 ambulatory patients with chronic HF who died due to cardiovascular causes and 200 patients who were alive at the end of the trial (after a median follow‐up period of 3.9 years). We measured baseline plasma concentrations of six previously identified high‐risk ceramide species [Cer(d18:1/16:0), Cer(d18:1/18:0), Cer(d18:1/20:0), Cer(d18:1/22:0), Cer(d18:1/24:0), and Cer(d18:1/24:1) and their individual plasma ratios with Cer(d18:1/24:0)]. Patients who died due to cardiovascular causes had significantly ( P  < 0.05 or less) higher levels of plasma Cer(d18:1/16:0) and Cer(d18:1/24:1), but lower levels of plasma Cer(d18:1/22:0) and Cer(d18:1/24:0) than had those who did not. All plasma ratios of each ceramide with Cer(d18:1/24:0) were significantly higher in patients who died due to cardiovascular causes. In Cox regression analyses, all five plasma ratios of each ceramide with Cer(d18:1/24:0) were significantly associated with a greater risk of cardiovascular mortality (with unadjusted hazard ratios ranging from 1.23 to 1.59; P  < 0.001 or less). These significant associations were attenuated after adjustment for multiple established risk factors, New York Heart Association functional class, left ventricular ejection fraction, use of medications, plasma pentraxin‐3 levels, and, especially, plasma N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) levels. When we applied a Bonferroni correction for multiple comparisons (using a P ‐threshold 0.05/5 ceramide ratios = 0.01), none of the five plasma ratios of each ceramide with Cer(d18:1/24:0) remained statistically associated with the risk of cardiovascular mortality (with adjusted hazard ratios ranging from 1.10 to 1.23). Conclusions: Higher levels of specific plasma ceramides [especially when used in ratios with Cer(d18:1/24:0)] are associated with increased cardiovascular mortality in ambulatory patients with chronic HF. However, these associations are weakened after adjustment for established cardiovascular risk factors, medication use, and plasma NT‐proBNP concentrations.